ANALISIS PENGARUH STRUKTUR MODAL DAN RISIKO OPERASIONAL TERHADAP TINGKAT PROFITABILITAS PADA PERUSAHAAN ASURANSI DI INDONESIA - Wiwin Erna Ekawati (Universitas Katolik Widya Karya Malang, 2020)
Research using data of insurance companies in Indonesia.analysis of capital structure produces insignificant effectCapital structure to Operational Risk. the results of the studyshow that changes in capital structure have no significantimpact on operational risk of an insurance company. This isbecause in the group of insurance companies make the capitalstructure is not a determining factor increase or decrease theoperational risk of a company.Broadly speaking the source of funds used in the capitalstructure is the liabilities in the balance sheet consisting ofown capital and long-term debt. The capital structure is notoptimal will cause a large capital cost. When using debt as anelement of financing then have to pay interest, where theinterest rate is higher with increasing debt. Influence is notsignificant Capital structure to Profitability shows thatchanges Capital structure has no significant impact on theprofitability of an insurance company.Operational Risk has a positive and significant effect onProfitability. Means the greater the operational risk of thecompany faced then the profitability will also increase. At thetime the company takes into account any risk factorsencountered, including the operational risk factors derivedfrom the internal company, then the maximum profitabilitylevel will also be obtained. Proper and timely use of long-termdebt and in accordance with the strength of the company willhave a major impact on the level of profitability of a company.Significant Influence Operational Risks to Profitabilityindicate that changes in Operational Risks have a significantimpact on the profitability of an insurance company.